Rheological Properties and Age-Related Changes of the Human Vitreous Humor - Tram, Nguyen K.; Swindle-Reilly, Katelyn E. (Frontiers in Bioengineering and Biotechnology, 2018)
The vitreous humor is a fragile, transparent hydrogel situated between the lens and the retina, occupying 80% of the eye’s volume. Due to its viscoelastic behavior, the vitreous serves as a mechanical damper for the eye, absorbing impacts and protecting the lens and retina. The vitreous liquefies with age, which compromises its function as a shock absorber and causes complications including retinal detachment, macular hole, and vitreous hemorrhage. Studies on the viscoelastic properties of the vitreous have been limited. Rheological testing of the vitreous has commonly been done on non-primate mammalian species. Human vitreous rheological properties have been previously reported; however, various measurement techniques were used, resulting in data that differed by orders of magnitude. Shear rheometry is commonly used to characterize soft tissues and hydrogels such as the vitreous humor. However, no human vitreous rheological data have been reported using this technique, preventing direct comparison to other published work. Additionally, no age-related changes in the mechanical properties of the human vitreous humor have been reported. Human vitreous samples (n=39, aged 62±15 years) were tested using a shear rheometer. Small amplitude oscillatory shear and creep experiments were performed. The linear viscoelastic region of the human vitreous was found to be below 1% strain. The solid phase of the old human vitreous was found to be stiffer than the young human vitreous and the porcine vitreous. The stiffness of the human vitreous gel also appeared to be positively correlated with age. Vitreous dehydration due to a decrease in hyaluronic acid concentration with age was proposed to cause the stiffening of the solid phase of the vitreous gel. Vitreous liquefaction, therefore, might be characterized as a simultaneous increase in liquid volume and localized stiffening of the vitreous gel. The phase separation of the vitreous humor with age has been hypothesized as the cause of many vitreous-related complications. This study provides viscoelastic properties and age-related changes of the human vitreous humor, which will aid in the design of biomimetic vitreous substitutes, enhancement in analyzing intravitreal transport of therapeutics, and understanding the pathological conditions of the vitreous humor.